A better way to prevent surgical complications after laryngectomy. Issue 1 (January 2022) - Boyapati, Raghuram; Gill, Tanisha; Ainkaran, Gayatree; Mahendran, Krishantini; Bisase, Brian; Norris, Paul; Davies-Husband, Cameron; Upile, Navdeep; Gulati, Aakshay; Butler, Daniel
Abstract : Introduction: 1. Understanding the implications of post-operative vomiting on the rate of salivary leak amongst patients undergoing laryngectomy. 2. Developing a better way to prevent post-operative vomiting through creation of a departmental policy to minimise risk of vomiting. Methods: We carried out a retrospective study of 24 patients who underwent primary or salvage laryngectomies. A Microsoft Excel sheet data containing the age, sex, smoking status, medical comorbidities, laryngectomy type, reconstructive method and the complications were all recorded. vomiting and the antiemetics particularly in the initial 48 hour period was documented. Results: 19 were male and 5 were female . Age varied from 51-86 and 14 of these patients were smokers. 8 patients had radiotherapy and this was within the 3 year period prior to laryngectomy in all patients. 16 patients had primary and 8 underwent salvage. Reconstructive methods included pectoralis major regional flap in 10 and ALT free flap in 6 patients. 8 patients had direct closure. 4 patients who developed a salivary leak had the post-op vomiting in the first 48 hours contrasting with 7 of the 18 who didn't have the salivary leak but had post-operative vomiting.The average length of stay amongst those receiving regular anti-emetics was 16 days compared to thenon anti emeticgroup of 23 days. Conclusions: Standardisation of the post-operative anti-emetic protocol would likely reduce the risk of post-operative vomiting with the aim to reduce the rate of salivary leak. We are developing a policy of the prescription of anti-emetics on regular side of drug chart for all laryngectomy patients.